Assessing the quality of life among African medical and health science students using the WHOQOL-BREF tool - Fatima Alzahra Galgam; Adil Abdalla; Mahmoud Shahin; Magda Yousif; Nahla Abdulrahman; Fatmah Alamoudi; Mehrunnisha Ahmad; Amira Yahia; Mohammad Sidiq; Aksh Chahal; Fuzail Ahmad; Mohammad Abu Shaphe; et al. (PeerJ)
Background The quality of life (QoL) among health professional students is available in the literature, yet there is a paucity of information concerning QoL among African students. The study aimed to measure the QoL with the World Health Organization Quality of Life-BREF (WHOQOL-BREF) tool among African medical and health science students. Methods A cross-sectional study was conducted involving 349 African medical and health science students from various disciplines at the International African University in May 2024. A purposive sampling method was used to recruit participants from five different faculties. Data were collected using the WHOQOL-BREF tool, and analyzed using descriptive statistics, chi-square test and multiple linear regression to determine the predictors of QoL among students. Results The overall QoL among 349 African medical and health science students was moderate, with a mean score of 67.5% ± 10.8%. The highest mean scores were observed in the physical health domain (69.3% ± 12.0%), while the lowest scores were in the environmental domain (62.9% ± 12.0%). The multiple regression analysis using demographic data as predictors of QoL revealed that dentistry students were significant predictors of higher overall QoL scores compared to other student groups (β = 7.059, p < 0.05), as well as specific QoL domains including physical health (β = 6.328), psychological health (β = 8.415), social relationships (β = 7.823), and environment (β = 7.017). Furthermore, students from the fields of laboratory sciences and medicine significantly predicted higher scores in the physical health domain (β = 5.223) and the psychological health domain (β = 4.433), respectively. Age was also a significant predictor; students aged between 20 and 23 years showed a positive impact on social relationship domain of QoL (β = 10.296). However, second year (β = −11.146), third year (β = −13.629), and fourth-year students (β = −10.144) exhibited lower social relationship domain of QoL scores. Conclusion Students of medical and health sciences in Africa exhibited moderate quality of life (QoL). The findings indicate that dentistry students generally experience higher QoL across multiple domains, which contrasts with students from other disciplines, such as pharmacy and nursing. Age and academic year were also significant predictors of QoL, with younger students and those in their initial years of study reporting lower scores. These results align with existing literature and underscore the need for targeted interventions to support students, particularly those in high-stress disciplines or at earlier stages of their education.